Neonatal Risk Factors for ASD and ADHD and Therapeutic Regimens for their Management in Children and Adolescent - R. Mohammad, Shumoos; M. Anwer, Zinah; A. Saleem, Zainab (Journal of the Faculty of Medicine Baghdad, 2024)
Background: Attention deficit hyperactivity disorder (ADHD) and autism spectrum disorder (ASD) are both neurodevelopmental disorders that affect children early in life. Both conditions have a complicated origin. Objectives: This study aims to evaluate the neonatal complications linked with ASD and ADHD and to outline the utilization of psychotropic medications in the management of children and adolescents with ASD. Methods: This study was conducted from January to April 2022 at the National Center for Autism/Medical City Complex in Baghdad. It involved 120 children with neurodevelopmental disorders and 120 control participants. A questionnaire was used to collect the data, which was then analyzed using SPSS 25. Results: Five perinatal factors have significant associations with child behavioral disorders, as indicated by a P-value of less than 0.05. These factors are Low birth weight (LBW), newborn complications, preterm birth, being the last child, and children delivered via a cesarean section. Additionally, the types of behavioral disorders have significant associations with the use of psychotropic medications. Around 50% of children with both ASD and ADHD, as well as children with ADHD alone, have used psychotropic medications. By comparison, only about 27% of children with ASD have used these medications. Conclusions: Neonatal risk factors may be linked to neurodevelopmental disorders. Medications are used to manage ASD and ADHD in children and youth.